Smartphone habit and behavior in Brunei: Personalization, gender, and generation gap. - Anshari, M.; Alas, Y.; Hardaker, G.; Jaidin, J.H.; Smith, M.; Ahad, A.D. (Computers in Human Behavior, 2016)
A smartphone is a device which offers advanced technologies, functions similarly to a computer, supports multitasking and makes it easy to remain connected with others. The following survey design research examined the usage patterns of smartphone users across different demographics. The results of this study provide insights into the prevalence of respondents’ usage of smartphones and their habits and behavior related to smartphone use itself especially among the younger generation of social disorders such as nomophobia and phubbing. In addition to documenting the experience of smartphone users, the research also examines personality patterns related to smartphone usage, the trends of different age groups, and the effects of gender preferences.